Used Car Lot - Thomas Hart Benton (artist):::Creator::::::::::::
Illustration of the Used Car Lot from The Grapes of Wrath, vol.1 p.74, illustrated edition, by Thomas Hart Benton, a native of eastern Oklahoma, who was assigned to draw archetypal Oklahomans for 20th Century Fox as the studio believed that would make the casting more accurate. "Goin' to California? Here's jus' what you need. Looks shot but they's thousan's of miles in her. Lined up side by side. Good used cars. Bargains. Clean, runs good."